Biologi Scelio pembertoni Timberlake (Hymenoptera: Scelionidae) pada telur Oxya japonica (Thunberg) (Orthoptera: Acrididae) - Hapsah Adawiyatul Qodir; Nina Maryana; Pudjianto Pudjianto (Jurnal Entomologi Indonesia, 2017)
The egg parasitoid, Scelio pembertoni Timberlake (Hymenoptera: Scelionidae), is an obligate endoparasitoid of Acrididae. One of the hosts of S. pembertoni is the eggs of Oxya japonica (Thunberg)(Orthoptera: Acrididae). The objectives of this research were to determine the development stage of S. pembertoni, longevity and fecundity, and the preference of S. pembertoni against different host age. S. pembertoni were collected from O. japonica eggs taken from cultivated and wild taro fields in Bogor area. The life cycle of S. pembertoni consisted of egg stage, first and second instar larval stage, pre-pupal and pupal stage, and adult stage. The first instar larva was teleaform and transparent white. The second instar larva was hymenopteriform and transparent white. The immature stage of S. pembertoni lasted within 27–33 days under laboratory condition, and was consisted of egg development period, first instar stage, second instar stage, pre-pupal stage, and pupal stage was 1.8, 4.95, 4.25, 5.40, and 12.85, respectively. Longevity of the adult females was 7–17 days, and longevity of the male adults was 3–11 days. The average fecundity of the females was 29.53 eggs. The sex ratio (male to female) of S. pembertoni during observation in the laboratory was 1 : 3.19.  The parasitisation level and the number of offsprings produced by S. pembertoni was higher on younger host eggs than the older ones.